Reinforcement Technology and Construction Technology of High Rise Building Structure - Xiaoming Lu, Liujun Fan (Forest Chemicals Review, 1970)
The stability of building structure and the importance of reinforcement technology seriouslyaffect the safety of high-rise buildings. In this paper, based on an actual project, the reliability ofthe original structure before reinforcement is identified and analyzed. According to the results ofreliability evaluation, some suggestions on the reinforcement design of the structure are putforward. According to the stress principle of the structure, the appropriate reinforcement form isselected and the reinforcement design is carried out. In this paper, the reinforced concretenonlinear finite element analysis of the whole process of reinforcement is carried out for atypical frame beam in the project. This paper studies and summarizes the constructiontechnology of structural reinforcement. Practice has proved that the effect of structuraltransformation is good.